Sistem Monitoring dan Control Suhu Kelembapan Pada Jamur Tiram Berbasis Internet Of Thing(IOT): Sistem Monitoring dan Control Suhu Kelembapan Pada Jamur Tiram Berbasis Internet Of Thing(IOT) - Arif Setiawan Penulis; Untung suryadhianto; Charis Fathul Hadi (ZETROEM, 2020)
The results of a survey I conducted by oyster mushroom cultivators in the Perangan Hamlet, Purwoharjo District, were still manual in controlling and controlling room temperature. The optimal temperature in the growth phase of mushrooms requires temperatures between 26°C-28°C with humidity between 70% RH-90% RH. Along with the rapid development of technology, temperature and humidity regulation and monitoring can be done automatically remotely with the concept of Internet Of Thing (IOT) Measuring temperature and humidity using the DHT22 sensor. The acquisition of measurement data is sent to the web using the ESP8266 which is connected to the internet.